Trends of Abortion Care Utilization in a Medical College of Western Region of Nepal - Shrestha, R; Adhikari, P (Journal of Gandaki Medical College-Nepal, 2018)
Introduction: Unsafe abortion is one of the important issues in reproductive and women’s health in developing countries. Social values and stigmas have much role and have been obstacle in countries like Nepal for the utilization of safe abortion services. Objectives: This study helps to provide brief overview of the pattern of abortion and its associated factors in a centre providing safe abortion services. Methods: This is a retrospective study carried out in Gandaki Medical College Teaching Hospital after reviewing the records of all the women who underwent Manual Vacuum Aspiration (MVA). Age, gravida, week of gestation and type of abortion were noted and analysed. Results: Maximum number of women belonged to age group of 25-29 and is primigravida. Most of them presented at fifth to ninth weeks of gestation and had incomplete abortion. Conclusions: Awareness and education regarding the availability of safe abortion services and its practice would improve the women’s reproductive health and well being. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 14-16